Gaya Komunikasi Generasi Z: Pengaruhnya di Lingkungan Kantor - Syarifah, Fathya Nazwa Uziani; Cahyana, Novalinda Imaniyar; Harmon Chaniago (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the communication style of Generation Z (Gen Z) in the workplace and its impact on organizational dynamics. Gen Z, born between 1997–2012, grew up in the digital era and brings unique characteristics such as reliance on technology, a preference for flexibility, and a strong need for collaboration and inclusion. This research employs a literature review method with a qualitative approach to synthesize findings from various sources. The results indicate that Gen Z tends to adopt a collaborative communication style ("The Relinquishing Style"), values face-to-face interaction despite being tech-savvy, and demands organizational culture adaptation—particularly in terms of work flexibility, transparency, and mental health support. Key challenges include the technological gap with older generations, differing work values, and resistance to traditional hierarchical structures. The study concludes by highlighting the importance for organizations to integrate inclusive policies, improve intergenerational digital literacy, and create work environments that support work-life balance in order to maximize Gen Z’s potential.